Tempo de defasagem entre a produção de serrapilheira e variáveis micrometeorológicas no norte do Pantanal Mato-Grossense - Carvalho, Ana Cristina Xavier de (2019)
Tropical forests are biomes that shelter diversities of animal and plant species, and that, in order to maintain its functioning and equilibrium, it needs energy to maintain itself. The biomass present in the ecosystems is a great example of a source of nutrients that supplies the vegetation and contributes to the maintenance and operation of the same. However, natural changes such as seasonal climatic changes or anthropic interference alter the natural functioning of the forests and thus affect these natural processes of energy flow and mass, thus influencing not only the dynamics of litter, but also the functioning ecosystems, thus discharacterizing and compromising their harmony. The objective of this work was to analyze the influence of micrometeorological variables on litter production through the time of lag in the Vochysia divergens Pohl area in the northern Pantanal of Mato Grosso in the year 2012. And for the evaluation of the degree of relationship between the variables were made Spearman's correlation test. There was no significant difference in litter production considering the horizontal and vertical arrangements, in the month to month period of the year by the Wilcoxon test (p <0.05). It was observed seasonality in the production of litter with higher values in the dry period. There was a lag time between litter production and micrometeorological variables, and litter production was more influenced by air temperature and accumulated precipitation in the seventh month thereafter. The vapor pressure deficit had a greater influence on the production of litter. litter in the ninth and tenth month and the relative humidity in the fourth, fifth and sixth months.